1993
DOI: 10.1007/bf01064929
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal atrophy in early Alzheimer's Disease: Anatomic specificity and validation

Abstract: We evaluated three groups of elderly individuals who were carefully screened to rule out clinically significant diseases that could affect cognition. They were matched for age and education. The groups included normals (N = 18), Alzheimer's Disease (AD) patients (N = 15), and minimally impaired individuals with memory complaints and impairments but who did not fulfill criteria for AD (N = 17). Volumetric measurements of different regions of the temporal lobe on the coronal scan as well as ratings of the perihi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 31 publications
5
57
0
2
Order By: Relevance
“…8 Stereological counts of mean total numbers of GFAPimmunopositive astrocytes in hippocampal formation of wildtype and dtg APP/PS1 mice aged 15-23 months (n=7-8/group). Asterisks indicate significant genotype effect (Ãp<0.01, ÃÃ p < 0.001); there was no significant effect of gender of Aβ-containing plaques in cortical brain regions to assist in the early clinical diagnosis of AD (Convit et al 1993;Benveniste et al 1999;Dedeoglu et al 2004). Previous studies using T1ρ("T-1-rho")-weighted MRI have been moderately successful in demonstrating Aβ-containing plaques in vivo based on local variations in protein content (Poduslo et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Stereological counts of mean total numbers of GFAPimmunopositive astrocytes in hippocampal formation of wildtype and dtg APP/PS1 mice aged 15-23 months (n=7-8/group). Asterisks indicate significant genotype effect (Ãp<0.01, ÃÃ p < 0.001); there was no significant effect of gender of Aβ-containing plaques in cortical brain regions to assist in the early clinical diagnosis of AD (Convit et al 1993;Benveniste et al 1999;Dedeoglu et al 2004). Previous studies using T1ρ("T-1-rho")-weighted MRI have been moderately successful in demonstrating Aβ-containing plaques in vivo based on local variations in protein content (Poduslo et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Stereological and neurochemical studies of brain tissue from patients with AD have confirmed widespread astrocytosis and microgliosis in cortical brain regions and significant reductions in neurotransmitter-specific subcortical nuclei, including the locus coeruleus (LC) and dorsal raphe (DR), and diminished concentrations in their cortical projections of corresponding monoamine neurotransmitters, norepinephrine (NE) and 5-hydroxytrptamine (5-HT); in contrast, these parameters remain relatively stable in brains of persons that undergo normal (non-demented) brain aging (Aletrino et al 1992;Mouton et al 1994;Storga et al 1996;Zarow et al 2003;Tuppo and Arias 2005). The strongest correlations with dementia severity have been reported in the loss of cortical volume (atrophy), observed by either ante-mortem or post-mortem analyses, and the reduction in cortical synapses (de la Monte 1989;DeKosky and Scheff 1990;Terry et al 1991;Convit et al 1993;Jobst et al 1994;Stout et al 1996;Mouton et al 1998;Zarow et al 2003;de Leon et al 2004). Thus, the evidence to date indicates that, while the diagnosis of AD depends heavily on the presence of amyloid plaques in neocortical brain regions, the progression of AD dementia appears to correlate more closely with degeneration of subcortical neurotransmitter systems that project to cortex, cortical synapse loss, and reduction of cortical volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Several volumetric MR studies have recently been published in the neuroradiology literature [6][7][8][9][10][11][12][13][14].lt is remarkable how few of these studies have inyolved the use of phantoms with known volumes to gauge the accrracy of the techniques employed. In many cases, the structure being measured (the hippocampus or TL in a living host) was not available for verification of measured volumes, and the researchers relied solely on (intraclass) correlation coefficients or similar tests to assess the veracity of their findings [91.…”
Section: Drscusstonmentioning
confidence: 99%
“…Another earlier study investigated hippocampal atrophy in normals, patients with AD, and minimally impaired individuals (with a MMSE 4 23, Global Deterioration Scale (GDS) of 3), Clinical Dementia Rating (CDR) of 0.5). 195 Significantly smaller hippocampi differentiated the minimally impaired individuals from the control group. People with mild cognitive impairment are at a higher risk for developing AD.…”
Section: Mild Cognitive Impairmentmentioning
confidence: 99%